Analisis Penerapan Sistem Manajemen Mutu Iso 9001:2015 Dalam Mempengaruhi Kualifikasi Akademik Karyawan (Studi Kasus Pada PT Sarana Utama Adimandiri) - Lalang Dintara; Shofiyaturrohmah Shofiyaturrohmah; Aulia Deswita; Rafli Alfariz (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In the facing of both consumer demand and global competition, the quality of products or services produced by companies should be noted as consumers' awareness of the quality of products or services is increasing. For this reason the company needs to get international recognition regarding the ordinary quality management, the iso 9001:2015 certification. Consistent application will affect customer or customer loyalty. Here the role of peak management is crucial to understanding market conditions and demand and to devise appropriate strategies for achieving corporate goals. The study aims to depict the application of the iso 9001:2015 quality management system in the mainstream of the adisystem, analyzing the impact of its application to support corporate engineering activities in obtaining project contracts, and the factors that support and implement these. The type of research used is descriptive and analysed by qualitative methods. Data collection techniques are conducted by observation, documentation, and interviews with selected informants by select sampling methods.